Confronting potential future augmentations of the physiologically equivalent temperature through public space design: The case of Rossio, Lisbon. (February 2018) - Nouri, A. Santos; Lopes, A.; Costa, J. Pedro; Matzarakis, A.
Highlights: Physiologically equivalent temperature is applied to examine outdoor comfort levels. 'What if?' agenda used to consider aggravations of current bioclimatic conditions. Thermophysiological stress grades adapted to consider various bioclimatic scenarios. Study results enable public space design options to be physiologically assessed. Abstract: When considering cities such as Lisbon, which due to their Köppen Geiger classification of ' Csa ', witness hot and dry summers, the translation of local bottom-up knowhow upon climatic guidelines has been a topic of considerable dissemination over recent years. Depicting upon a concrete case study located in Lisbon's historical quarter, the results from a previous bioclimatic study undertaken by the authors were taken further in order to consider how worst-case-scenarios of climate change (A1FI/RCP8.5) could potentially impact the existing human thermal environment within the square. In addition to considering its existing layout, public space design interventions were also examined within different thermal/temporal scenarios through the use the Physiologically Equivalent Temperature (PET) and PET(Load) indices. The results of the study revealed that within a climatic worse-case-scenario, and without any adaptive measures to address Physiological Stress (PS) levels, the majority of the square presented potential PS thresholds ranging between 'Extreme Heat Stress Lv.3/4′, with PET values exceeding that of 51 °C and 56 °C. On the other hand, and particularly in regions prone to high levels of solar radiation, the thermal amelioration effects of the proposed public space design interventions presented reductions of PET values up to 16.6 °C.